Mobile Application Intervention Effectiveness in Improving Hypertensive Patients Medication Adherence: A Systematic Review - Nur Hannan Najihah Mohamad Tawpik; Hussam Abdeljabar Ahmad Mizher; Syahrir Zaini (Journal of Pharmacy)
Introduction: Hypertension and its complications are massive global health issues.  Major limitations in hypertensive patients’ treatment include suboptimal blood pressure control and nonadherence to medication. The popularity of telemedicine has risen in recent years. Mobile phone applications intervention in particular, provides features including medication-taking, refilling reminders, and biometric results tracker resulting in better health outcomes and improved medication adherence. This review aims to assess the effectiveness of mobile application in improving adherence in hypertensive patients. Methods: PubMed, Scopus, and Cochrane Library were searched with filters applied for studies published between 2013 and 2023 and content published in English with the keywords; telemedicine, mobile apps, medication adherence, and hypertension. These keywords were joined using Boolean operators for an effective search. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis Statement was followed for this systematic review. The Mixed Method Appraisal Tool was used to assess the quality of the included studies. The data was extracted by the authors and validated by another for accuracy and completeness. Results: Twelve studies ranging from moderate to high quality were included in this review. A total of 10 studies showed a statistically significant improvement (p < 0.001) in medication adherence with mobile apps intervention. The combined apps features from the mobile apps empower patients to be more adherent, involved and informed about their treatment progress. Conclusion: Hypertensive patients’ medication adherence improved with mobile apps intervention. However, the heterogeneity of adherence measurement methods and apps functionality in the included studies calls for further studies to determine the effectiveness of specific mobile apps feature as well as the standardisation of the adherence measurement method used.